Structure-specificity relationship of cardiac glycosides as a substrate for glucohydrolase II - Terada, Yukimasa; Misoi, Rumi; Watanabe, Naoharu; Hornberger, Martin; Kreis, Wolfgang (Chemical & Pharmaceutical Bulletin, 2000)
Cardenolide glucohydrolase II (CGH II) is a cardenolide-specific glucohydrolase obtained from Digitalis lanata leaves. We investigated the structure-specificity relationship of several cardenolide disaccharides as a substrate for CGH II. Conformation analysis of the substrates was performed using molecular mechanics calculations. The sugar chain conformation of two inert glycosides was significantly different from that of the other glycosides. The other two glycosides, which were weak substrates of CGH II, were suggested to have an intramolecular hydrogen bond between the sugar groups. It was deduced that this hydrogen bond restricts the conformational change of the sugar chain and prevents the glycosides from enzymatic recognition.
UnivIS-Import:2015-03-06:Pub.2000.nat.dbio.LPB.struct
Keywords: Cardenolide glucohydrolase II (CGH II); Cardiac glycoside; Conformation analysis; Molecular mechanics; Structure- specificity relationship